British Archaeology Abroad, 1966: British School of Archaeology in Jerusalem - Hennessy, Basil
Jordan; i.a. “During May 1966, Mrs Diana Helbæk excavated a Chalcolithic site in the Beqa‘a of the Lebanon. The excavations have produced important evidence of the extent of the Halaf culture of Mesopotamia into this region during the late 5th and early 4th millennia B.C.”